Succesful Management of the Pregnancy Complicated with Thrombophilia, Uterine Unicollis and Previous Pregnancy Loss: A Case Report - Sertaç Esin; Sinan Beksaç; Sevim Balcı (Medical Network, 2006)
A 28 years old multigravid admitted to our maternal fetal medicine unit because of a second trimester loss of pregnancy due to preterm labor at 28 week. Her obstetrical history was uneventful. Ultrasonographic examination revealed a unicornuate uterus with rudimentary horn. Hyperhomocysteinemia caused by MTHFR heterozy gosity and decrease in Protein S levels were found by blood analysis. Low dose aspirine and LWM Heparin were started 6 weeks bef ore conception. Follow-up of the pregnancy in the functional unicornus resulted in a healthy baby delivered by cesarean section at 37 week due to chronic intrauterine hypoxia and uterine anomaly.